Rom, Italien. Ein neues Forschungsprojekt auf dem Kapitol in Rom. Grabungen im Garten des ehemaligen preußischen Hospitals, Kampagne 2018 - Aglietti, Silvia; Beste, Heinz; Blanco, Alessandro; Dally, Ortwin; Danti, Alberto; Manfrecola, Karoline; Manzo, Pamela; Nepi, Daniele; Parisi Presicce, Claudio; Tanganelli, Roberta; Zagari, Francesca (e-Forschungsberichte des DAI, 2020)
A first campaign of a new project on the Capitoline Hill took place between July and September 2018 on the southwestern tip of the Capitol Hill in Rome including geophysical prospections, excavations in the garden behind the first Institute’s building and the former Protestant Hospital of 1836 and a beginning documentation of the remaining architectural ruins of the temple of Iuppiter Optimus Maximus. The research of a three-week measuring campaign was going to focus on the topography and the complex architectural history and remains, like the fundaments of the Iuppiter Optimus Maximus temple. An italian version of the article written by the same authors will be published in the Bullettino della Commissione Archeologica Comunale di Roma.